1998
DOI: 10.1103/physrevb.58.7076
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic recombination dynamics in shallow quantum wells

Abstract: We report a comprehensive study of carrier-recombination dynamics in shallow Al x Ga 1Ϫx As/GaAs quantum wells. At low crystal temperature ͑2 K͒, the excitonic radiative recombination time is shown to be strongly enhanced in shallow quantum wells with xϾ0.01, consistently with a model that takes into account the thermal equilibrium between the three-dimensional exciton gas of the barrier and the two-dimensional exciton gas, which are closer in energy as x decreases. Furthermore, we demonstrate the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…As a result, Auger effects are negligible in the cooling analysis in bulk GaAs below 100 K, whereas they are still appreciable in the determination of b τ at lower temperatures. Available experimental measurements of non-radiative lifetime in GaAs-based QWs [29,30] give values between 1 ns and 10 ns which is two orders of magnitude shorter than b τ shown in Fig. 5.…”
mentioning
confidence: 80%
“…As a result, Auger effects are negligible in the cooling analysis in bulk GaAs below 100 K, whereas they are still appreciable in the determination of b τ at lower temperatures. Available experimental measurements of non-radiative lifetime in GaAs-based QWs [29,30] give values between 1 ns and 10 ns which is two orders of magnitude shorter than b τ shown in Fig. 5.…”
mentioning
confidence: 80%
“…In our approach, 60 Ph. Roussignol et al [1] are also reported electrons, holes and excitons form ideal and dilute gases described by Boltzmann distribution functions. These ideal gases are at thermal equilibrium with each other and characterized by a single, time dependent, temperature.…”
mentioning
confidence: 96%
“…Recent time-resolved photoluminescence experiments, performed on shallow GaAs/ Ga 1± ±x Al x As quantum wells with x as low as 1%, have revealed that good samples display a photoluminescence decay time, t r , which increases with decreasing x [1]. On the contrary, an accurate theory of excitons in these structures reveals that very little variations with x are expected for the oscillator strength of the excitonic transition if x`3% [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations